Research on Measurement System of High-Frequency Parameters for Line Traps - Wensi Cao; Chuanjin Huang; Guozhi Zhang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The composing of high frequency line trap of power system is briefly introduced, A new method based on improved voltage meter method is presented, which can measure the frequency-impedance characteristic of the line trap of power system. A new testing arithmetic is presented based on the correlation principle, Cross-correlation functions of the two measured signals are directly computed and some properties about correlation and sine function are adopted to separate the useful signals from the part noises，so the measurement accuracy is improved, A group of practical formulas for calculating the impedance and resistive component is summarized ,the MATLAB simulation of the arithmetic is presented . Using DSP chip TMS320LF2407 and A/D chip THS12082 as the core of the measurement system, its software and hardware are designed. Analyze the Given K-type broadband tuning traps which has typical parameters. Experimental results and theoretical analysis demonstrate the measurement system can obtain a precision of better than 1％ and has a good ability of anti-jamming DOI: http://dx.doi.org/10.11591/telkomnika.v11i7.2933